1982
DOI: 10.1063/1.1136939
|View full text |Cite
|
Sign up to set email alerts
|

Multichannel switch triggered by low-voltage auxiliary discharges

Abstract: A verylowinductance triggered multichannel surface switch Rev. Sci. Instrum. 61, 852 (1990); 10.1063/1.1141453 Multichannel switch triggered by saturable reactorinduced voltage pulse Rev. Sci. Instrum. 54, 765 (1983);

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1982
1982
2005
2005

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Multichannel railgaps using a variety of triggering methods have been investigated thus far. [1][2][3][4][5] As for multichannel gap switches, the shorter the formative and statistical time lags of each gap, the larger the number of arc channels. As we examined the breakdown characteristics of a sphere/plane gap using a mirror-finished brass plate and a porous metal as plane electrodes, we confirmed that the formative and statistical time lags decrease when porous metals are used as a discharge electrode, 6) so the number of arc channels of a self-breakdown-type railgap with a porous metal is expected to increase.…”
Section: Introductionmentioning
confidence: 99%
“…Multichannel railgaps using a variety of triggering methods have been investigated thus far. [1][2][3][4][5] As for multichannel gap switches, the shorter the formative and statistical time lags of each gap, the larger the number of arc channels. As we examined the breakdown characteristics of a sphere/plane gap using a mirror-finished brass plate and a porous metal as plane electrodes, we confirmed that the formative and statistical time lags decrease when porous metals are used as a discharge electrode, 6) so the number of arc channels of a self-breakdown-type railgap with a porous metal is expected to increase.…”
Section: Introductionmentioning
confidence: 99%